The Experience of EFL Pre-service teachers in Creating Multimedia of PACIFIC Through TPACK Framework on Technology in Education Course Academic Year 2018/2019 - Sabarinah; Effendi Limbong; Iwan Setiawan (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2019)
The purposes of this study were to find the EFL pre-service teachers' experience, obstacle and solution in creating multimedia of PACIFIC through TPACK framework. The design of this study was a qualitative case study that aimed to interpret the phenomenon that happened about the experience of pre-service teachers in creating multimedia of PACIFIC through TPACK framework. This study used semi-structured interview, direct observation and the video project of PACIFIC as the document. Research participants were selected using purposive sampling. The participants of this study focus group discussion. The researcher found that the pre-service teachers already knew the software of PACIFIC but they did not know how to use the software of PACIFIC except PowerPoint. In creating multimedia of PACIFIC pre-service teachers need to design the project then they did teaching practice in the class. According to those processes they faced several obstacles: for the first time met PACIFIC they did not know how to operate the features of the software, their confusion to determine the activities that appropriate to their topic and their nervousness when they did teaching process. Based on those obstacles they had their solutions: they used internet to search the tutorial how to use those software and they had Facebook group contains many information about those software, they considered the learning purposes, the context of students' level and they just pretended like they present the material in front of their friends.